Apparent Increasing Lithium Diffusion Coefficient with Applied Current in Graphite. Issue 12 (28th August 2020) - Dees, Dennis W.; Rodrigues, Marco-Tulio F.; Kalaga, Kaushik; Trask, Stephen E.; Shkrob, Ilya A.; Abraham, Daniel P.; Jansen, Andrew N.
Abstract : In this study, we assert that the apparent lithium diffusion coefficient in graphite active particles in the negative electrodes of lithium-ion cells increases appreciably with the intercalation rate. This assertion is based on an electrochemical model analysis of a wide range of electrochemical micro-reference electrode full cell studies on a coated natural graphite and other literature results. While the mechanism for this increase is a subject of further investigation, the results of our study suggest that the lithium transport in the graphite does not limit the maximum attainable charging rate in typical lithium-ion cells for electric vehicles.